Strategi Penguatan Motivasi Belajar Bahasa Arab melalui Kompetisi: Evaluasi Darunnajah Language Competition - Imam Khairul Annas (Universitas Darunnajah, Jakarta, Indonesia, 2025)
This study aims to evaluate the impact of the Darunnajah Language Competition (DLC) on the motivation to learn Arabic among santri at Pondok Pesantren Darunnajah. The research uses a descriptive quantitative approach, with a survey method to collect data on the motivation of santri before and after participating in the DLC. The study involves 34 respondents, consisting of 18 female and 16 male santri who participated in the 7th DLC in 2025. Data was collected through questionnaires designed to assess the motivation levels and factors influencing their motivation in learning Arabic. The results showed that before the DLC, most santri had a moderate to high level of motivation. After participating in the competition, there was a significant increase in motivation, with 44.1% of santri reporting a very high level of motivation. Furthermore, a majority of participants felt more confident in speaking Arabic after the competition. The competition format, which included a variety of Arabic language-related events, played a crucial role in maintaining interest and engagement in learning. Social support, especially from peers and the surrounding environment, significantly influenced the increase in motivation, with over 70% of santri reporting the importance of their social environment in motivating them. Additionally, the competitive nature of DLC contributed to greater enthusiasm and involvement in learning Arabic, making the competition an effective tool for language development.In conclusion, the DLC has proven to be an effective strategy for enhancing the motivation to learn Arabic among santri, with significant contributions from social support and the engaging competition format. The study recommends continuing such competitions with more diverse and attractive events to further motivate santri in their Arabic language learning journey.